Hand, foot and mouth disease - a short case report - Kashyap, Roopashri-Rajesh (J Clin Exp Dent, 2015)
Hand, foot and mouth disease, that was once considered a disease of cattle, has been emerging as a common human childhood disease in the last few years. It is a viral disease characterized by a brief febrile illness and typical vesicular rashes. In rare cases, patients may also develop neurological complications. This report describes a case of hand, foot and mouth disease, presented with typical clinical features in the South Indian region. Key words:Hand, foot and mouth disease, viral lesions, blisters.